Análise morfométrica de 900 discos intervertebrais lombares obtida a partir de imagens de ressonância magnética - análise de altura discal anterior e posterior - Onishi, Franz Jooji [UNIFESP] (2019)
Introduction: ​Degenerative diseases of the lumbar spine usually affect the most distal segments - L3-L4, L4-L5 and L5-S1. The lumbar fusion is one of the most commonly performed spinal procedures in the world, and interbody fusion has been one of the most effective strategies. There is a lack of cataloging of data regarding intervertebral disc height in Brazilian population and surgical implant materials are usually imported from other countries or are manufactured in Brazil based on foreign models​. Objective: 1) To evaluate and describe the height pattern of normal intervertebral discs in a Brazilian population. 2) To analyze the adequacy of dimensions of inter-market devices available in the market to our population. 3) To analyze the difference in anterior and posterior height of the cited discs, evaluating the role of this difference in the formation of lumbar lordosis. 4) Analyze individuals of different genders, ethnic and age groups and describe the peculiarities of each subgroup. 5) To propose a coefficient to 6 calculate the ideal ratio between anterior and posterior height in the different segments studied, obtained by dividing the anterior and posterior height of the discs. ​Methods: A retrospective study based on analysis of images obtained in lumbar spine magnetic resonance imaging. We included male and female patients who underwent lumbar spine resonance. Patients with previous surgeries, advanced degenerative disc disease, suspected infection, deformities were excluded from the study. ​Results: 300 patients had their images analyzed for the anterior and posterior height of the L3-L4, L4-L5 and L5-S1 discs, totaling 900 intervertebral discs. The mean anterior disc height of L3-L4 was 9.30 mm, L4-L5 10.94 mm and L5-S1 12.41 mm. About 7% of the patients have a L3-L4 anterior height less than 7mm, which is ​usually the smallest available cage height. The ​ratio obtained by dividing the anterior height by the posterior height was 1,43 for L3-L4; 1,57 for L4-L5 and 1,93 for L5-S1. ​Conclusions: L3 to S1 discs present greater anterior height than posterior and this difference tends to decrease with aging. The L5-S1 disc is that most contributes for lumbar lordosis, followed by L4-L5. Populations with lower average height should have their disc dimensions carefully studied during surgical planning, ​especially in L3-L4 segment.